Nano flame retardant and flame retardant epoxy resin composite material
By using layered polyphosphazene-titanium carbide nanomaterial P-MX@UIO as the nanofire retardant, the problems of heat release and toxic flue gas during combustion of epoxy resin are solved, and the effect of significantly improving flame retardant performance and maintaining mechanical properties at low addition amounts is achieved.
Patent Information
- Application Number
- CN202310624890.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-30
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2043-05-30
AI Technical Summary
Existing epoxy resins release a large amount of heat and toxic flue gas during combustion, limiting their application potential, and the dispersion problem of existing nanofire retardants in epoxy resin composites leads to limited flame retardant performance.
The layered polyphosphazene-titanium carbide nanomaterial P-MX@UIO is used as the nanofire retardant. This material forms an MX/PZS structure through hydrogen bonding and grows MOFs in situ to improve flame retardant performance and dispersion.
At a lower addition amount (≤4 wt%), P-MX@UIO significantly reduces the heat release rate and toxic flue gas output of the epoxy resin, while maintaining the mechanical properties of the matrix material, and its flame retardant effect is better than that of existing ternary nanocomposite flame retardants.
Smart Images

Figure CN116554695B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of flame-retardant composite materials, and in particular relates to a nano flame retardant and flame-retardant epoxy resin composite material. Background Art
[0002] Epoxy resin (EP), as an advanced thermosetting polymer, has excellent mechanical properties, electrical insulation properties, bonding properties and flexibility. It is widely used in manufacturing fields such as coatings, adhesives, semiconductor packaging, electronic circuit boards and composite matrix. However, EP releases a large amount of heat and toxic and harmful smoke during combustion, which seriously limits its application potential. The development of EP composite materials with superior properties of high fire resistance, light smoke and low toxicity is a research focus in the field of flame retardancy. In particular, it is crucial to reduce the emission of toxic gases and smoke particles generated during the decomposition of EP in order to meet the requirements of environmental protection and safe production. In order to solve this problem, researchers often use the method of adding fillers to improve the flame retardant properties of EP.
[0003] Since the 1990s, nanocomposite technology has attracted widespread attention in the field of flame retardancy. The incorporation of nanoparticles such as graphene, molybdenum disulfide, carbon nanotubes and boron nitride can effectively improve the flame retardant properties of EP. Compared with traditional flame retardants, the dosage of nanofillers is relatively low (usually <5wt%), so it has higher flame retardant efficiency. Adjusting the structure and composition of nanofillers can further achieve the suppression of toxic smoke.
[0004] MXene nanosheets, hereinafter referred to as MX nanosheets, have a highly thermally stable layered structure and can act as a rigid barrier to prevent the transfer of decomposed fragments, thereby improving the fire safety of polymers. However, the flame retardant effect of a single MX is limited, and it is difficult to effectively reduce the heat release rate of EP and the production of toxic smoke. MX can play an excellent barrier catalytic role in the polymer matrix at extremely low content, but it has poor compatibility with the flame retardant matrix interface. For example, based on the excellent barrier catalytic effect of MXene nanosheets, this research group has developed a ternary nanocomposite flame retardant epoxy resin and a preparation method thereof, see the patent CN202111188005.8. The components of the ternary nanocomposite flame retardant include MXene nanosheets, layered double metal hydroxides and cuprous oxide nanocubes. The obtained composite flame retardant is applied to the flame retardant modification of epoxy resin, and certain results have been achieved, which inhibits the release of heat and toxic smoke during the combustion of epoxy resin to a certain extent. However, the dispersion problem of the flame retardant itself has caused limitations in its flame retardant properties in epoxy resin composites.
[0005] Metal organic frameworks (MOFs) are new nanomaterials self-assembled by transition metal ions and organic ligands through coordination bond bridging. Thanks to their rich pore structure and catalytic sites, MOFs show good application prospects in the field of flame retardancy. However, the poor stability of most MOFs limits their application. The above problems can be solved by hybridizing with nanomaterials with high thermal stability.
[0006] As an emerging organic-inorganic polymer material, polyphosphazene has excellent flame retardant effect due to the abundant phosphorus and nitrogen atoms in the main chain, which can significantly reduce the heat release rate and smoke release of the polymer. The non-flammable gases such as N2 and NH3 generated by polyphosphazene during combustion and degradation can dilute the concentration of combustible gases. Therefore, the hybrid composite structure of MX, MOFs and polyphosphazene can exert a synergistic flame retardant effect and achieve a significant enhancement of the flame retardant properties of the polymer. Summary of the invention
[0007] In order to overcome the shortcomings of the above-mentioned prior art, the present invention provides a layered polyphosphazene-titanium carbide nano flame retardant P-MX@UIO, which has the characteristics of both inorganic and organic flame retardant materials and has good multi-element flame retardant effect. The nano flame retardant is introduced into a polyester polymer matrix material, which can exert better flame retardant properties without affecting the mechanical properties of the matrix material at a lower addition amount (≤4wt%); the polyester polymer matrix material described in the present invention includes epoxy resin, polyurethane, unsaturated polyester, bismaleimide resin, and polyethylene terephthalate.
[0008] The technical solution adopted by the present invention is:
[0009] In a first aspect, the present invention provides a nano flame retardant, wherein the nano flame retardant is a layered polyphosphazene-titanium carbide nanomaterial P-MX@UIO, such as Figure 1a As shown, the nano flame retardant is prepared by self-assembly of polyphosphazene nanosheets, i.e., PZS nanosheets and MX nanosheets driven by electrostatic force to form an MX / PZS structure, and loading UIO66 nanoparticles on the surface of the MX / PZS structure by in-situ growth; the MX / PZS structure is an MX / PZS hybrid sheet structure, and the UIO66 nanoparticles are UIO66 nanocubes with a size of 100 to 200 nm.
[0010] like Figure 1c As shown, the PZS nanosheet is prepared by a hydrothermal method using hexachlorotripolyphosphazene HCCP and a first ligand as raw materials, wherein the first ligand is any one of barbituric acid, phloroglucinol and cyanuric acid;
[0011] like Figure 1bAs shown, the MX nanosheet is obtained by etching the MAX phase raw material with a mixed solution of lithium fluoride and hydrochloric acid and then peeling it off; it should be noted that in the MAX phase, M represents a transition metal element, A represents a main group element, and X represents carbon or nitrogen, which has a wide variety, including but not limited to Ti3AlC2, Mo3AlC2, Ti3AlCN, V2AlC, V4AlC3, Nb2AlC, Nb4AlC3, Ta2AlC; as a preferred embodiment of the present invention, the MAX phase is Ti3AlC2, and the correspondingly prepared MXene, i.e., MX nanosheet, is Ti3C2T x ;
[0012] The UIO66, as a MOFs material, is loaded on the surface of the PZS nanosheet and the MX nanosheet by a hydrothermal method. As a preferred preparation method, the loading step includes: dispersing the MX nanosheet and the PZS nanosheet in DMF, wherein the mass volume ratio of MX to DMF is 1g:(100-150)ml, and ultrasonically stirring for 1-2h; then adding ZrCl4, phenyl carboxylic acid ligands and polyvinyl pyrrolidone PVP, stirring ultrasonically at room temperature for 1-2h, placing in a hydrothermal reactor, and hydrothermally reacting at 100-130°C for 10-12h. ; Finally, the product P-MX@UIO is obtained by drying; wherein the mass ratio of MX to PZS is (1:1) to (1:1.5); the ratio of phenyl carboxylic acid ligands to MX is (1:1) to (1:1.5); the mass ratio of ZrCl4 to phenyl carboxylic acid ligands is (1.3:1) to (2:1); the mass ratio of ZrCl4 to PVP is (1.8:1) to (3:1); wherein the phenyl carboxylic acid ligands include terephthalic acid, trimesic acid, trimesic acid, 2-aminoterephthalic acid, trimellitic acid and 1,2,4,5-benzenetetracarboxylic acid;
[0013] Principle of the invention: The layered polyphosphazene-titanium carbide nanomaterial P-MX@UIO provided by the present invention adopts a hydrogen bond induced assembly strategy to obtain a 2D-2D, i.e., sheet + sheet MX / PZS structure, which is used as a substrate for in-situ growth of MOFs to obtain the final ternary flame retardant. Compared with the strategy of growing MOFs on the surface of a single type of nanosheet, the agglomeration of the final prepared product due to the strong intermolecular force of MOFs itself can be avoided. PZS has abundant hydroxyl groups, which is helpful for the adsorption of phenylcarboxylic acid ligands and Zr 2+ MOFs can be grown in situ to avoid their agglomeration. In addition, MX nanosheets can serve as a physical barrier layer to further inhibit the agglomeration of MOFs, thereby reducing the adverse effects of MOFs on matrix properties such as mechanical properties when they are doped into polyester polymer matrix materials as flame retardants.
[0014] Moreover, the ternary flame retardant provided in the present application is used for polyester polymer matrix materials, and can give the polyester polymer matrix materials better flame retardant properties while maintaining good mechanical properties of the matrix materials; since there are more hydroxyl functional groups on the surface of PZS nanosheets, the dispersion of the ternary flame retardant in the matrix material can be promoted, and the hydroxyl functional groups and the organic molecular chains of the polyester polymer matrix materials have good compatibility. Secondly, the hydroxyl functional groups can participate in the curing reaction of the polyester polymer matrix materials, further improving the dispersion so as to better exert the flame retardant effect.
[0015] Preferably, the preparation steps of the polyphosphazene PZS nanosheets include: using barbituric acid as the first ligand, ultrasonically dispersing hexachlorotripolyphosphazene HCCP and barbituric acid in acetonitrile, and the mass volume ratio of HCCP to acetonitrile is 0.5g: (25-50) mL, and stirring for 0.5-1h; then pouring the mixed solution into a hydrothermal kettle, placing it in an oven at 150-200°C, and hydrothermally reacting it for 22-25h; finally, drying the hydrothermal product in a vacuum dryer for 10-12h to obtain PZS powder; wherein the mass ratio of HCCP to barbituric acid is (1:1)-(1:2.5);
[0016] Preferably, the preparation steps of the MX nanosheets include: first dissolving lithium fluoride powder in hydrochloric acid, and the mass volume ratio of lithium fluoride to hydrochloric acid is 1g: (20-60)mL; adding titanium aluminum carbon powder to the mixed solution, keeping stirring, and reacting in a water bath at 35-45°C for 24-48h; then centrifuging the product and washing the product with deionized water until the pH value reaches 6-7; finally dispersing the product in water for 1-2h and placing it in a centrifuge for centrifugal separation at a speed of 3500-4500rpm to obtain a dispersion of MX nanosheets; wherein the mass ratio of lithium fluoride to titanium aluminum carbon is (1:1)-(1:3); the concentration of hydrochloric acid is 6-9mol / L, and the concentration of the dispersion of MX nanosheets is 3.5-4.8mg / mL.
[0017] In a second aspect, the present invention provides a flame retardant epoxy resin composite material, wherein the flame retardant epoxy resin composite material is prepared by high temperature curing method using the following raw materials in parts by weight:
[0018] Epoxy resin EP 78.8-80.4 parts;
[0019] Curing agent 17.2-18.6 parts;
[0020] 1 to 4 parts of the above-mentioned nano flame retardant;
[0021] Wherein, the curing agent is preferably 4,4' diaminodiphenylmethane; the EP and the nano flame retardant are preferably mixed in any of the following weight ratios: 78.8:4, 79.6:3, 80.4:2. The flame retardant is preferably added in an amount of 2-4wt% in the raw materials, and most preferably 4wt%. As a preferred embodiment, the epoxy resin composite material of the present invention is mixed and configured by the following weight parts of raw materials: 78.8 parts of EP, 17.2 parts of curing agent, and 4 parts of the above flame retardant. The EP composite material configured with this component has a high comprehensive performance level in both flame retardancy and mechanical properties.
[0022] In a third aspect, the present invention also provides a preferred method for preparing the flame retardant epoxy resin composite material, comprising the following steps:
[0023] Step S1, stirring acetone and the flame retardant in an ultrasonic disperser at a dispersion temperature of 50 to 80° C. for 2 to 4 hours to obtain a dispersion, wherein the mass volume ratio of the flame retardant to acetone is 1 g: (30 to 50) mL;
[0024] Step S2, adding EP heated to 80-100° C. to the dispersion obtained in step S1, continuing stirring for 3-5 hours, and putting into an oil bath pot after mixing evenly, and volatilizing acetone at 85-95° C. for 2-5 hours to obtain an EP dispersion;
[0025] Step S3, add curing agent to the EP dispersion of step S2, keep stirring for 10 to 20 seconds, then quickly pour it into a mold, put it into a high-temperature oven for curing, keep the temperature at 90 to 120° C. for 2 to 3 hours, raise the temperature to 30 to 150° C. for 2 to 3 hours, and wait for natural cooling to obtain flame-retardant EP.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] 1. The nano flame retardant provided by the present invention is a multiphase functional nano flame retardant, which has layered nanosheets and metal organic frameworks, and can play the role of sheet barrier, cross-linking carbonization and catalytic detoxification, thereby improving flame retardant performance;
[0028] 2. The multiphase functionalized nano flame retardant provided by the present invention has high flame retardant efficiency and good smoke suppression effect on EP, and has broad application prospects in flame retardant polymers. Specifically, the P-MX@UIO nano flame retardant shows higher efficiency in reducing heat release rate and smoke generation rate. After adding 4.0wt% of P-MX@UIO, the peak heat release rate and total heat release amount are reduced to 679.9kW / m 2 and 72.88MJ / m 2 The maximum smoke production rate and total smoke production are also 0.44m 2 / s and 32.08m 2 .
[0029] 3. The flame retardant of the present invention contains hydroxyl groups, which can participate in the curing reaction of EP. On the one hand, the good compatibility between hydroxyl groups and the organic molecular chains of epoxy resin is used to improve the dispersion of nanoparticles in the matrix. On the other hand, the polymerization reaction between hydroxyl groups and epoxy groups is used to enhance the interfacial force between the flame retardant and the matrix, ensuring that the flame retardant will not precipitate or volatilize over time, thereby achieving the improvement of flame retardancy while ensuring mechanical properties.
[0030] 4. Compared with a ternary nano-composite flame retardant previously developed by this research group and disclosed in patent CN202111188005.8, the P-MX@UIO flame retardant provided by the present invention has the advantages of small addition amount and high flame retardant effect on EP, which is also a flame retardant EP for epoxy resin preparation. The present invention adds 4wt% of nano flame retardant, and the peak heat release rate, total heat release, maximum smoke production rate and total smoke production of EP are significantly reduced, which are reduced by 53.5%, 51.8%, 45.0% and 54.1% respectively. In the above-mentioned prior patents, when the flame retardant additive is 6wt%, its maximum heat release rate is only reduced by 43.42%, and the total heat release is only reduced by 31.22%, and its high addition amount also significantly weakens the mechanical properties of EP. Therefore, the flame retardant effect of the flame retardant provided by this application is significantly better than the ternary nano-composite flame retardant disclosed in the above-mentioned patent. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1a Schematic diagram of the preparation method of the nano flame retardant;
[0032] Figure 1b Schematic diagram of the preparation method of the MX nanosheet;
[0033] Figure 1c Schematic diagram of the preparation method of the PZS nanosheet;
[0034] Figure 2 This is the electron microscope image of MX prepared in Example 2;
[0035] Figure 3 This is an electron microscope image of the PZS prepared in Example 1;
[0036] Figure 4 This is an electron microscope image of UIO66 prepared in Comparative Example 3;
[0037] Figure 5 This is the electron microscope image of P-MX@UIO prepared in Example 3.
[0038] Figure 6It is the elemental mapping spectrum and EDS results of P-MX@UIO prepared in Example 3;
[0039] Figure 7 is the overall spectrum of the X-ray photoelectron spectrum of P-MX@UIO prepared in Example 3;
[0040] Figure 8 is the C1s spectrum of the X-ray photoelectron spectrum of P-MX@UIO prepared in Example 3;
[0041] Fig. 9 is the N1s spectrum of the X-ray photoelectron spectrum of P-MX@UIO prepared in Example 3;
[0042] Fig.10 is the P2p spectrum of the X-ray photoelectron spectrum of P-MX@UIO prepared in Example 3;
[0043] Fig.11 is the O1s spectrum of the X-ray photoelectron spectrum of P-MX@UIO prepared in Example 3;
[0044] Fig.12 is the Zr3d spectrum of the X-ray photoelectron spectrum of P-MX@UIO prepared in Example 3;
[0045] Fig.13 is the Ti2p spectrum of the X-ray photoelectron spectrum of P-MX@UIO prepared in Example 3;
[0046] Fig.14 The FTIR spectra of PZS prepared in Example 1, UIO66 prepared in Comparative Example 3, and P-MX@UIO prepared in Example 3 are shown;
[0047] Fig.15 The thermal degradation process of UIO66 nanoparticles in air in Examples 1-3 and Comparative Example 3; Fig.16 The thermogravimetric test results of the commercially available epoxy resin and the flame-retardant epoxy resin prepared by the comparative examples 1-3 and the application examples 1-2 under air;
[0048] Fig.17 The thermogravimetric test results under nitrogen of the commercially available epoxy resin and the flame-retardant epoxy resin prepared by the comparative examples 1-3 and the application examples 1-2, respectively;
[0049] Fig.18 The heat release rate of the commercially available epoxy resin and the cone calorimetry test of the comparative application examples 1-3 and the application examples 1-2;
[0050] Fig.19 The total heat release of commercially available epoxy resin and application examples 1-3 and application examples 1-2 in cone calorimetry tests;
[0051] Fig. 20 The smoke generation rate of the commercially available epoxy resin and the application comparison examples 1-3 and the application examples 1-2 in the cone calorimetry test;
[0052] Fig.21 The total smoke production of commercial epoxy resin and application examples 1-3 and application examples 1-2 in cone calorimetry tests; Fig. 22 The CO generation rate of the commercially available epoxy resin and the application comparison examples 1-3 and the application examples 1-2 in cone calorimetry test;
[0053] Fig.23 The total CO release of commercially available epoxy resins and application examples 1-3 and application examples 1-2 in cone calorimetry tests;
[0054] Fig.24 It is a comparison chart of the storage modulus of the dynamic mechanical analysis performance of commercially available epoxy resins and application comparative examples 1-3 and application example 1;
[0055] Fig.25 It is a comparison chart of the loss tangent of the dynamic mechanical analysis performance of commercially available epoxy resins and application comparative examples 1-3 and application example 1;
[0056] Fig.26 These are the test results of mechanical tensile properties of flame-retardant epoxy resins prepared with pure epoxy resin and the same amount of PZS, UIO66, MX and P-MX@UIO. DETAILED DESCRIPTION
[0057] The present invention is further described below in conjunction with the accompanying drawings.
[0058] In order to further illustrate the technical scheme of the present invention, the preferred embodiments of the present invention are described below in conjunction with examples, but it should be understood that these descriptions are only to further illustrate the features and advantages of the present invention, rather than to limit the claims of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. At the same time, the raw materials or reagents mentioned below that are not described in detail are all commercially available products, and the process steps or methods not mentioned in detail are all process steps or methods known to those skilled in the art.
[0059] The sources of some raw materials and reagents involved in the following embodiments, application examples and test examples are as follows: HCCP, barbituric acid, acetonitrile, lithium fluoride, hydrochloric acid, DMF, ZrCl4, terephthalic acid, PVP, acetone, and 4,4'-diaminodiphenylmethane were all purchased from Sinopharm Chemical Reagent Co., Ltd.; titanium aluminum carbon powder was purchased from Jilin Yiyi Technology Co., Ltd.; EP was purchased from Wuxi Qianguang Chemical Raw Materials Co., Ltd.
[0060] Example 1 Preparation of PZS Nanosheets
[0061] 0.7g HCCP and 0.77g barbituric acid were ultrasonically dispersed in 50ml acetonitrile and stirred for 1h. The mixture was then poured into a hydrothermal kettle and placed in an oven at 150°C for 22h of hydrothermal reaction. Finally, the hydrothermal product was dried in a vacuum dryer for 12h to obtain PZS powder.
[0062] Example 2 Preparation of MX Nanosheets
[0063] First, 1g of lithium fluoride powder was dissolved in 30mL of hydrochloric acid, and 1g of titanium aluminum carbon powder was added to the mixture, which was stirred and reacted in a 35°C water bath for 24h. The product was then centrifuged and washed with deionized water until the pH value reached 7. Finally, the product was dispersed in water and ultrasonicated for 1h, and then placed in a centrifuge for centrifugal separation at a speed of 4500rpm to obtain a dispersion of MX nanosheets. The concentration of hydrochloric acid was 6mol / L, and the concentration of the dispersion of MX nanosheets was 3.6mg / mL.
[0064] Example 3 Preparation of P-MX@UIO Nanomaterials
[0065] 1g of MX and 1g of PZS were dispersed in 150ml of DMF and stirred with ultrasound for 1h. Then 1.1g of ZrCl4, 0.8g of terephthalic acid and 0.6g of PVP were added, stirred with ultrasound for 1h at room temperature, placed in a hydrothermal reactor, and hydrothermally reacted at 130℃ for 10h. Finally, the product P-MX@UIO nanomaterial was obtained by drying.
[0066] Application Example 1 Preparation of EP / 2.0P-MX@UIO epoxy resin composite material
[0067] 2 g of P-MX@UIO powder was dispersed in acetone, and after ultrasonic treatment in a flask for 1 h, 80.4 g of EP( was added and stirred for 30 min. The flask was placed in a 90°C oil bath and stirred to evaporate the acetone. 17.6 g of molten 4,4'-diaminodiphenylmethane was added and stirred for 30 s. The mixture was poured into a mold, and the mold was placed in an oven for curing. The curing temperature was 100°C for 2 h, then raised to 150°C for 2 h, and cooled naturally to obtain the flame-retardant epoxy resin EP / 2.0P-MX@UIO. In this application example 1, 4,4'-diaminodiphenylmethane was used as a curing agent.
[0068] The P-MX@UIO powder in this application example 1 is the P-MX@UIO nanomaterial prepared in Example 3, and the incorporation mass percentage of P-MX@UIO is 2%, that is, the mass ratio of P-MX@UIO: (epoxy resin + curing agent) is 2:98, wherein the mass ratio of epoxy resin to curing agent is 4.58:1.
[0069] Application Example 2 Preparation of EP / 4.0P-MX@UIO epoxy resin composite material
[0070] This application example 2 is also a method for preparing a flame retardant epoxy resin. The difference from application example 1 is that the mass percentage of P-MX@UIO added is 4%. Specifically, 4 g of P-MX@UIO powder is dispersed in acetone, and after ultrasonic treatment in a flask for 1 hour, 78.8 g of epoxy resin is added and stirred for 30 minutes. The flask is placed in a 90°C oil bath and stirred to evaporate the acetone. 17.2 g of molten 4,4'-diaminodiphenylmethane is added and stirred for 30 seconds. The mixture is poured into a mold, and the mold is placed in an oven for curing. The curing temperature is 100°C for 2 hours, then the temperature is raised to 150°C for 2 hours, and the flame retardant epoxy resin EP / 4.0P-MX@UIO is obtained by naturally cooling.
[0071] Preparation of EP / 2.0PZS epoxy resin composite material using comparative example 1
[0072] The only difference from Application Example 1 is that PZS nanoparticles are used to replace P-MX@UIO to obtain the sample EP / 2.0PZS, wherein the PZS nanoparticles are prepared as in Example 1.
[0073] Preparation of EP / 2.0MX epoxy resin composite material using comparative example 2
[0074] The only difference from Application Example 1 is that MX nanoparticles are used instead of P-MX@UIO to obtain sample EP / 2.0MX, wherein the MX nanoparticles are prepared as in Example 2.
[0075] Preparation of EP / 2.0UIO66 epoxy resin composite material using comparative example 3
[0076] It is basically the same as Application Example 1, except that UIO66 nanoparticles are used instead of P-MX@UIO to obtain sample EP / 2.0UIO66. The preparation process of UIO66 nanoparticles is as follows: 1.1g ZrCl4, 0.8g terephthalic acid, and 0.6g PVP are ultrasonically dispersed in 150ml DMF. After stirring at room temperature for 1h, the mixture is placed in a hydrothermal reactor and subjected to hydrothermal reaction at 130°C for 10h. Finally, UIO66 powder is obtained by freeze drying.
[0077] Figure 2-5 The electron microscope images of nano flame retardants and their intermediates are shown; Figure 2 The electron microscope image of MX prepared in Example 2 is shown, and its two-dimensional lamellar structure can be seen; Figure 3 The electron microscope image of the PZS prepared in Example 1 is shown, and a block structure formed by stacking of flakes can be seen; Figure 4The electron microscope image of UIO66 prepared in Comparative Example 3 is shown, and the nano-square morphology can be seen;
[0078] Figure 5 The electron microscope image of P-MX@UIO prepared in Example 3 is shown, and it can be found that it is composed of UIO66 nanocubes, PZS and MX nanosheets; Figure 6 This is the element mapping spectrum and EDS results of P-MX@UIO prepared in Example 3. It can be observed that the uniform distribution of C, O, N, P, Zr, and Ti elements. Figure 7 This is the overall spectrum of the X-ray photoelectron spectrum of P-MX@UIO prepared in Example 3, from which signals of C, Ti, O, N, F, P, and Zr can be seen; Figure 8 is the C1s spectrum of the X-ray photoelectron spectrum of P-MX@UIO prepared in Example 3. The peaks at 288.58, 286.68, 285.58, 284.78, and 281.38 eV correspond to C=O, CO, CN, CC / CH, and C-Ti bonds; Fig. 9 This is the N1s spectrum of the X-ray photoelectron spectrum of P-MX@UIO prepared in Example 3. The peaks at 401.68, 400.58, 399.88, 399.18 and 398.18 eV correspond to C=N, P=N, -NH2, PNH-PH and PN=P bonds; Fig.10 This is the P2p spectrum of the X-ray photoelectron spectrum of P-MX@UIO prepared in Example 3. The peaks at 134.48 and 133.58 eV correspond to NP=N and PO bonds, proving the existence of PZS. Fig.11 The O1s spectrum of the X-ray photoelectron spectrum of P-MX@UIO prepared in Example 3. The peaks at 532.48, 531.48 and 530.08 eV correspond to C=O, OH / C-Ti-O x and MO; Fig.12 This is the Zr3d spectrum of the X-ray photoelectron spectrum of P-MX@UIO prepared in Example 3. The peaks at 185.88 and 183.48 eV correspond to the Zr3d 3 / 2 and Zr3d 5 / 2 , proving the existence of UIO66. Fig.13 The Ti2p spectrum of the X-ray photoelectron spectrum of P-MX@UIO prepared in Example 3, the peak at 464.98 eV corresponds to the Ti-O bond, and the peaks at 461.48 and 455.88 eV correspond to the Ti 2+ Ti2p 1 / 2 and Ti2p 3 / 2 , 459.68 and 454.58 eV correspond to the Ti2p of the Ti-C bond 1 / 2 and Ti2p 3 / 2The above confirms the existence of MX, PZS and UIO66.
[0079] Fig.14 The FTIR spectra of PZS prepared in Example 1, UIO66 prepared in Comparative Example 3, and P-MX@UIO prepared in Example 3 are shown. 3120 cm -1 The nearby band is the NH bond, 2820cm -1 The bands nearby are CH bonds. 1530 and 1400 and 1000 cm -1 The nearby signals correspond to the presence of aromatic rings and CO bonds, which are the same in the results of UIO66 and P-MX@UIO. -1 The nearby bands confirm the presence of a P=N bond, while the signal at 862 cm-1 is associated with a PN bond. -1 The peaks near 794 and 754 cm are related to PO and Ar-PO. -1 The presence of HCN bonds is confirmed by the signals at 3410 and 1254 cm -1 The nearby bands are associated with OH and CN bonds. In addition, 1655 and 1578 cm -1 The bands at 745 and 666 cm are from C=O and OC=O bonds, while -1 The signal comes from the O-Zr-O bond. Regarding the spectrum of P-MX@UIO, the signals of OH, C=O, OC=O, P=N, PN, PO, Ar-PO, and O-Zr-O bonds are visible. It is worth noting that the 606 and 552 cm -1 The nearby bands correspond to Ti-O and Ti-C bonds. In short, the spectrum well contains the signals attributed to MX, PZS, and UIO66, confirming the successful preparation of P-MX@UIO.
[0080] Fig.15 The thermal stability of UIO66 nanoparticles in air in Examples 1-3 and Comparative Example 3 is shown. The specific test is to analyze the thermal stability of the samples in air using a TGAQ5000 thermogravimetric analyzer, with a heating rate of 20°C / min and a sample test mass of 2-6 mg. Fig.15As shown, a slight weight loss of 8.0 wt% was observed for MX, which was related to the removal of terminal groups and oxidation of metal sites. As for PZS, a significant weight loss of 72.8 wt% was observed due to its severe chain scission. In addition, two decomposition stages of UIO66 were found. The first stage before 442.5 °C was related to the departure of physically absorbed water, while the second stage between 442.5-800.0 °C was related to the removal of organic ligands. Regarding P-MX@UIO, a mild degradation was found with a mass loss of 30.8 wt%.
[0081] Figure 16-17 The thermogravimetric test results of commercial epoxy resin and flame retardant epoxy resin prepared by application examples 1-3 and application examples 1-2 under air and nitrogen respectively are shown. The specific thermogravimetric test is to analyze the thermal stability of samples under nitrogen and air by TGAQ5000 thermogravimetric analyzer, with a heating rate of 20°C / rain and a sample test mass of 2-6 mg.
[0082] Fig.16 This is the TGA curve of the sample in air environment. The carbon residue rate of pure epoxy resin is only 1.25%. After adding 2.0wt% of PZS, MX and UIO66, the carbon residue rates are increased to 2.82wt%, 2.67% and 3.02% respectively. After adding 2.0wt% of P-MX@UIO, the carbon residue rate of the resin reaches 3.22%. After adding 4.0wt% of P-MX@UIO, the carbon residue rate of the resin is further increased to 3.67%.
[0083] Fig.17 This is the TGA curve of the sample under nitrogen environment. The carbon residue rate of pure epoxy resin is 15.36%. After adding 2.0wt% of PZS, MX and UIO66, the carbon residue rates increased to 19.51%, 17.57% and 18.32% respectively. The carbon residue rate of the resin with 2.0wt% of P-MX@UIO reached 20.72%. After adding 4.0wt% of P-MX@UIO, the carbon residue rate of the resin further increased to 22.63%. P-MX@UIO showed a better carbonization effect.
[0084] The effect of P-MX@UIO nano flame retardant on the combustion hazard of epoxy resin was further studied by cone calorimetry test, and the commercially available epoxy resin was compared with application examples 1-3 and application examples 1-2. The results are as follows Figure 18-23 The specific cone calorimetry test is carried out on a cone calorimeter (UK, Fire Testing Technology) according to ISO5660 standard, and the sample size is 100×100×3mm 3 , electric spark ignition, thermal radiation flux is 35kW / m 2, calculate the heat release curve based on the oxygen consumption principle, and monitor parameters such as flue gas and CO release at the same time;
[0085] in, Fig.18 The heat release rate is shown; Fig.19 The total heat release is shown; Fig. 20 The smoke production rate is shown; Fig.21 The total smoke production is shown; Fig. 22 The CO production rate is shown; Fig.23 The total CO release is shown.
[0086] from Figure 18-23 It can be seen that the peak heat release rate, total heat release, maximum smoke generation rate and total smoke generation of pure epoxy resin are 1460.68kW / m 2 、151.25MJ / m 2 、0.8m 2 / s and 71.12m 2 , CO generation rate and total CO release were 0.05 g / s and 4.22 g, respectively. After adding nanoparticles, the total heat release, total smoke production and total CO release of epoxy resin decreased. Compared with PZS, UIO66 and MX, the use of P-MX@UIO can further reduce the total heat release, total smoke production and total CO release, which are 81.95 MJ / m 2 、0.41m 2 / s and 2.08g. In addition, using only 4.0wt% of P-MX@UIO, the peak heat release rate, total heat release, maximum smoke production rate and total smoke production decreased by about 53.5%, 51.8%, 45.0% and 54.1%, and the CO production rate and total CO release decreased by 40% and 51.4%, respectively. This shows that the use of P-MX@UIO can significantly inhibit the release of toxic gases during the combustion of epoxy resin.
[0087] Fig.24 and Fig.25 The dynamic mechanical analysis (DMA) performance diagram of commercially available epoxy resin and application examples 1-3 and application example 1 was collected using the American TAQ800DMA equipment, with a temperature range of room temperature to 250°C, a heating rate of 5°C / min, and a frequency of 1Hz. Fig.24 is a comparison chart of storage modulus, Fig.25 The comparison chart of loss tangent is shown below. At 57.0℃, the storage modulus of EP is low, at 1547.0MPa. After adding PZS, UIO66, and MX, the storage modulus of EP are 1937.8, 1603.1, and 2404.1MPa, respectively. With the replacement of P-MX@UIO, the storage modulus is further increased to 2573.3MPa, an increase of 39.9%. This shows that P-MX@UIO significantly improves the mechanical properties of the polymer.
[0088] Fig.26 These are the mechanical tensile properties test results of flame-retardant epoxy resins prepared by pure epoxy resin and the same amount of PZS, UIO66, MX and P-MX@UIO. The dark columns represent tensile strength and the light columns represent elongation at break. It can be seen that compared with pure epoxy resin, the tensile strength is increased by 84% after adding 2.0wt% P-MX@UIO, indicating that the addition of P-MX@UIO nano flame retardant can also enhance the mechanical properties of EP.
Claims
1. A nano flame retardant, characterized in that: The nano flame retardant is prepared by self-assembly of polyphosphazene nanosheets, i.e., PZS nanosheets and MX nanosheets, to form an MX / PZS structure through electrostatic force, and in-situ growth of UIO66 nanoparticles on the surfaces of the PZS nanosheets and the MX nanosheets through a hydrothermal method, i.e., the UIO66 nanoparticles are loaded on the surfaces of the PZS nanosheets and the MX nanosheets, and the formed UIO66 nanoparticles are UIO66 nanocubes with a size of 100-200 nm; the MX / PZS structure is an MX / PZS hybrid sheet structure; the MX nanosheets are obtained by etching a MAX phase raw material with a mixed solution of lithium fluoride and hydrochloric acid and then peeling it off; the PZS nanosheets are prepared by a hydrothermal method using hexachlorotripolyphosphazene HCCP and a first ligand as raw materials, and the first ligand is any one of barbituric acid, phloroglucinol and cyanuric acid.
2. A nano flame retardant according to claim 1, characterized in that: The MAX phase is Ti3AlC2, and the correspondingly prepared MX nanosheets are Ti3C2T x .
3. A nano flame retardant according to claim 1, characterized in that: The step of in-situ growing UIO66 nanoparticles on the surface of the PZS nanosheet and the MX nanosheet by a hydrothermal method comprises: dispersing the MX nanosheet and the PZS nanosheet in DMF, wherein the mass volume ratio of MX to DMF is 1g: (100-150) ml, and ultrasonically stirring for 1-2 hours; then adding ZrCl4, phenyl carboxylic acid ligands and polyvinyl pyrrolidone PVP, stirring ultrasonically for 1-2 hours at room temperature, placing in a hydrothermal kettle, and hydrothermally reacting at 100-130° C. for 10-12 hours; and finally drying to obtain the product P-M X@UIO; wherein the mass ratio of MX to PZS is (1:1)~(1:1.5); the ratio of phenylcarboxylic acid ligands to MX is (1:1)~(1:1.5); the mass ratio of ZrCl4 to phenylcarboxylic acid ligands is (1.3:1)~(2:1); the mass ratio of ZrCl4 to PVP is (1.8:1)~(3:1); wherein the phenylcarboxylic acid ligands include terephthalic acid, trimesic acid, 2-aminoterephthalic acid, trimellitic acid and 1,2,4,5-benzenetetracarboxylic acid.
4. A nano flame retardant as claimed in claim 1, characterized in that: The preparation steps of the polyphosphazene PZS nanosheets include: ultrasonically dispersing hexachlorotripolyphosphazene HCCP and barbituric acid in acetonitrile, wherein the mass volume ratio of the HCCP to the acetonitrile is 0.5 g: (25-50) ml, and stirring is maintained for 0.5-1 h; then pouring the mixed solution into a hydrothermal kettle, placing it in an oven at 150-200° C., and performing a hydrothermal reaction for 22-25 h; finally, drying the hydrothermal product in a vacuum dryer for 10-12 h to obtain PZS powder; wherein the mass ratio of HCCP to barbituric acid is (1:1) to (1:2.5).
5. A nano flame retardant as claimed in claim 1, characterized in that: The preparation steps of the MX nanosheets include: first dissolving lithium fluoride powder in hydrochloric acid, and the mass volume ratio of lithium fluoride to hydrochloric acid is 1g: (20-60) ml; adding titanium aluminum carbon powder to the mixed solution, keeping stirring, and reacting for 24-48 hours in a water bath at 35-45°C; then centrifuging the product, and washing the product with deionized water until the pH value reaches 6-7; finally dispersing the product in water for 1-2 hours, and then placing it in a centrifuge for centrifugal separation at a speed of 3500-4500rpm to obtain a dispersion of MX nanosheets; wherein the mass ratio of lithium fluoride to titanium aluminum carbon is (1:1)-(1:3); the concentration of hydrochloric acid is 6-9mol / L, and the concentration of the dispersion of MX nanosheets is 3.5-4.8mg / mL.
6. A flame retardant epoxy resin composite material, characterized in that: The flame retardant epoxy resin composite material is prepared by high temperature curing method using the following raw materials in parts by weight: Epoxy resin EP 78.8~80.4 parts; Curing agent 17.2~18.6 parts; 1 to 4 parts of the nano flame retardant according to any one of claims 1 to 5.
7. The flame retardant epoxy resin composite material according to claim 6, characterized in that: The curing agent is 4,4'-diaminodiphenylmethane.
8. The flame retardant epoxy resin composite material according to claim 6, characterized in that: The flame retardant is added in an amount of 2-4 wt % in the raw materials.
9. A flame retardant epoxy resin composite material as claimed in claim 6, characterized in that: The epoxy resin composite material is prepared by mixing the following raw materials in parts by weight: 78.8 parts of EP, 17.2 parts of curing agent, and 4 parts of the above-mentioned flame retardant.
10. A method for preparing a flame retardant epoxy resin composite material, characterized in that: The steps include: Step S1, stirring acetone and the nano flame retardant according to any one of claims 1 to 5 in an ultrasonic disperser at a dispersion temperature of 50 to 80° C. for 2 to 4 hours to obtain a dispersion, wherein the mass volume ratio of the flame retardant to acetone is 1 g: (30 to 50) ml; Step S2, adding EP heated to 80-100° C. to the dispersion obtained in step S1, continuing stirring for 3-5 hours, and putting into an oil bath pot after mixing evenly, and volatilizing acetone at 85-95° C. for 2-5 hours to obtain an EP dispersion; Step S3, adding a curing agent to the EP dispersion of step S2, keeping stirring for 10-20 seconds, then quickly pouring it into a mold, putting it into a high-temperature oven for curing, keeping the temperature at 90-120°C for 2-3 hours, raising the temperature to 30-150°C for 2-3 hours, and then naturally cooling down to obtain a flame-retardant EP.
Citation Information
Patent Citations
A ternary nanocomposite flame retardant, a flame-retardant epoxy resin and its preparation method
CN113845695B
Modified MOFs flame retardant, preparation method and application thereof
CN113045762A
Preparation of functionalized titanium carbide nano flame retardant and application of functionalized titanium carbide nano flame retardant in epoxy resin
CN115028897A